Negotiating Religious Gaps: The Enterprise of Translating Christian Tracts by Protestant Missionaries in Nineteenth-Century China. By John T. P. Lai - Pfister, Lauren F. (Literature and theology, 2014)
As international publications in Christian theology are now receiving serious attention in Mainland China as an academic discipline with substantial intellectual content and cross-cultural importance, there is also a reflective turn in reconsidering missionary and indigenous expressions of Christian theology and its related literature during the past 200 years. John Lai’s book is at the vanguard of this recent trend, offering a cross-disciplinary interpretive framework to understand these materials as well as a vast amount of systematically presented data that can stimulate future research.